Clinical Outcomes Associated with Co-infection of Carbapenem-Resistant Enterobacterales and other Multidrug-Resistant Organisms. Issue 4 (December 2022) - Tadese, Bekana K.; DeSantis, Stacia M.; Mgbere, Osaro; Fujimoto, Kayo; Darkoh, Charles
Summary: Background: Infections with carbapenem-resistant Enterobacterales (CRE) are associated with increased risk of death. Polymicrobial infections with antimicrobial-resistance may add to the burden of clinical care and patients' clinical prognosis. Aim: To examine the impact of CRE co-infection with other multi-drug resistant organisms (MDRO) on patient clinical outcomes. Study Design: A retrospective observational study was conducted to compare the clinical outcomes of CRE patients who were co-infected with carbapenem-resistant Pseudomonas aeruginosa (CRPA), multidrug-resistant Acinetobacter baumannii (MDRA) and Methicillin-resistant Staphylococcus aureus (MRSA). Results: A total of 224 CRPA and 209 MDRA co-infections with CRE were identified from 4, 236 cases from 2015-2020. The overall 90-day all-cause mortality was 21.6% but increased to 35.0% and 33.5% among patients who were co-infected with CRPA and MDRA, respectively. The odds of all-cause mortality among CRE patients who were co-infected with CRPA was twice that of patients identified with CRE alone [adjusted odds ratio (AOR) = 2.02, 95% confidence interval (CI): 1.18–3.46]. Further, the odds of all-cause mortality among CRE patients who were concomitantly identified with MRSA was more than twice that of patients who were not identified with MRSA [AOR = 2.16, 95%CI:1.31–3.56]. The clinical outcome of patients with CRE did not differ significantly depending on the presence of carbapenemase genes. Conclusion: The results show that CRPA and CRE co-infections have synergistic effects on clinical outcomes. Further investigation is necessary to understand the mechanism. Screening high risk patients for concomitant antimicrobial-resistant infections may have a significant clinical impact, including effective therapies, antibiotic stewardship, and infection control policies.